Reconstructing Holocene environmental change in Lake Ohrid (Macedonia/Albania) using diatom as proxies - Cvetkoska, Aleksandra; Levkov, Zlatko; Reed, Jane (Macedonian Journal of Ecology and Environment, 2012)
Lake Ohrid with its Tertiary origin and outstanding biodiversity and endemism represents a unique ecosystem containing valuable data for palaeoenvironmental reconstruction. Investigation of the time sequence of the Last glacial–interglacial transition and the Holocene epoch in the sediment core Co1202 (359–17 cm depth, ca. 14.6–0.3 ka BP) was performed. Diatom proxies were used to reconstruct environmental and climate changes preserved in the investigated time interval. Two major diatom biostratigraphic zones were recognized, comprising DZ 1 (359–158 cm depth, ca. 14.6–3.9 ka) and DZ 2 (158–17 cm depth, ca. 3.9–0.3 ka). Evidence for rapid climate events within these zones was also explored. The diatom response to the colder climate intervals is evidenced by the domination of the hypolimnetic, endemic species Cyclotella fottii. Warmer climate conditions are represented by increased dominance of the thermophilic taxon Cyclotella ocellata. The analysis is currently made at a relatively low temporal resolution; we also present evidence for short-lived shifts in diatom species assemblage composition which may represent climate disruptions between ca. 9–8 ka BP and ca. 6–5 ka BP, possibly linked to abrupt global climate events. Finally, evidence of increased phosphorus levels compared to the Last Interglacial is suggested by the first appearance during the Holocene of mesotrophic Stephanodiscus taxa.